The pattern of romantic and sexual related experiences among Chinese young adolescents: an exploration with multi-group latent class analysis - Chunyan Yu; Chaohua Lou; Qiguo Lian; Xiaowen Tu; Jiashuai Zhang; Xiayun Zuo (BMC, 2021)
Plain language summary Studies on teenagers' romantic and sexual experiences would help to prevent early sex arises before it really takes place. However, such studies are limited, especially in China. The traditional culture thought that youth should not start romance before college. This study used the Global Early Adolescent Study Shanghai site baseline data collected among1776 teenagers to explore their romantic and sexual experiences patterns and identify the influencing factors. There were significant gender differences in teenagers' romantic and sexual-related behaviors. According to the multi-group latent class analysis, we classified the teenagers into three classes: the general group, the early romance group, and the sex exploratory group. The multi-nominal logistic regression showed youth in the early romance group were more likely to had friends of both boys and girls, ever had boyfriend/girlfriend and were freer to go out than the general group; while boys in the sex exploratory group were older, ever had a boyfriend/girlfriend, believed it was normal for boys to be sexually active than girls, had more freedom to go out, and had less perception of care from school adults and neighborhood. Girls in the sex exploratory group were older and less likely to make decisions on their own. Given the result we found, we call for health researchers and educators to conduct sex education programs promoting more equal gender norms and provide services to help young adolescents get right information and strengthen their skills in communication, decision making and critical thinking.